2019
DOI: 10.1289/ehp4815
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Psychiatric Emergency Department Utilization and Fine Particulate Matter: A Case-Crossover Study

Abstract: Background:Acute exposure to ambient particulate matter <2.5μm in aerodynamic diameter (PM2.5) has been associated with adult psychiatric exacerbations but has not been studied in children.Objectives:Our objectives were to estimate the association between acute exposures to ambient PM2.5 and psychiatric emergency department (ED) utilization and to determine if it is modified by community deprivation.Methods:We used a time-stratified case-crossover design to analyze all pediatric, psychiatric ED encounters at C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 67 publications
(57 reference statements)
1
47
0
Order By: Relevance
“…While there are limited findings for the other mental health outcomes examined in our study, risk of increased psychotic disorders among adolescents is of particular importance partly because adolescents who experience psychotic symptoms are at an increased risk of other mental health conditions such as suicidal behavior or bipolar disorder [ 52 , 53 ]. Another recent study based in Cincinnati, Ohio found that short-term exposure to PM 2.5 was associated with increased risks of psychiatric emergency department visits related to schizophrenia, suicidality, adjustment, and anxiety disorders among adolescents [ 54 ]. The study found stronger associations for suicidality and anxiety-related ED visits among children who lived in socioeconomically deprived neighborhoods, which suggests that chronic exposure to neighborhood-level stressors may modify the relationship between air pollutants and mental health among children.…”
Section: Discussionmentioning
confidence: 99%
“…While there are limited findings for the other mental health outcomes examined in our study, risk of increased psychotic disorders among adolescents is of particular importance partly because adolescents who experience psychotic symptoms are at an increased risk of other mental health conditions such as suicidal behavior or bipolar disorder [ 52 , 53 ]. Another recent study based in Cincinnati, Ohio found that short-term exposure to PM 2.5 was associated with increased risks of psychiatric emergency department visits related to schizophrenia, suicidality, adjustment, and anxiety disorders among adolescents [ 54 ]. The study found stronger associations for suicidality and anxiety-related ED visits among children who lived in socioeconomically deprived neighborhoods, which suggests that chronic exposure to neighborhood-level stressors may modify the relationship between air pollutants and mental health among children.…”
Section: Discussionmentioning
confidence: 99%
“…A relatively neglected area concerning the risk of developing anxiety disorders includes environmental exposures, including air pollution (Brokamp, Strawn, Beck, & Ryan, 2019). Mercury and other toxicants are associated with an increased risk of developing anxiety disorders, even when correcting for maternal age at delivery, fish intake, maternal ethnicity, household income, maternal education, and marital status (Patel et al, 2019).…”
Section: Environmental Toxicants and Risk Factors For Developing Anximentioning
confidence: 99%
“…More recently, specific components of air pollution that induce inflammation and oxidative stress in the brain (e.g., particulate matter with an aerodynamic diameter < 2.5 µm (PM 2.5 )) have been linked to exacerbations of anxiety disorders. Greater PM 2.5 exposure is associated with an increased risk of psychiatric emergency department visits for anxiety disorders in children and adolescents, and community deprivation mediates this association (Brokamp et al, 2019).…”
Section: Environmental Toxicants and Risk Factors For Developing Anximentioning
confidence: 99%
“…A growing number of economic studies use quasi-experimental methods to estimate the causal effects of air pollution exposure on human health, using health metrics such as infant mortality and birth outcomes (e.g., Chay and Greenstone, 2003b;Currie and Neidell, 2005;Currie et al, 2009;Currie and Walker, 2011;Sanders and Stoecker, 2015;Arceo et al, 2016;Alexander and Schwandt, 2019), adult mortality (e.g., Deryugina et al, 2019;Anderson, 2020), respiratory problems (e.g., Moretti and Neidell, 2011;, and cardiovascular diseases (e.g., Halliday et al, 2019). While the focus of much of the literature has been on physical health, there is growing epidemiological work showing an association between air pollution and mental health (e.g., Sass et al, 2017;Kim et al, 2018;Brokamp et al, 2019).…”
Section: Air Pollution and Healthmentioning
confidence: 99%